Digital workplace transformation: Subtraction logic as deinstitutionalising the taken-for-granted - Zimmer Markus Philipp; Baiyere Abayomi; Salmela Hannu (Elsevier, 2025)
Digital technology enables the transformation of work and workplaces. Previous digital workplace transformation (DWT) literature has shown how organisations add new digital technologies to create new workplace routines. However, such an emphasis on addition may hinder scholarship from recognising that some established workplace technologies and routines must disappear for new ones to emerge. Adopting the concept of deinstitutionalisation, we examine the rationale for and the process of how an organisation abandons workplace routines that conflict with its intended DWT. Referring to this as subtraction logic, we advance two contributions. First, we conceptualise how deinstitutionalisation of established workplace routines and technologies unfolds in DWT by outlining a process model that synthesises addition and subtraction. Second, we highlight the underlying rationales for DWT. With these insights, we shift the gaze from the dominant addition logic, which advocates for appropriating new digital technologies, to the equally important value of subtraction, i.e., removing existing workplace technologies (or inscribed institutional rules) to abandon workplace routines that conflict with the intended DWT. Hence, our study highlights the oft-ignored subtraction logic in DWT.